The Effect of Situational Leadership and Motivation on Employee Performance: A Case Study of Vietnam Electricity Headquarters - Minh, Ngo Ngoc; Loc, Nguyen Duc (International Journal of Psychosocial Rehabilitation, 2020)
This paper is the result of case study at Vietnam Electricity Headquarters (EVN) which examines how situational leadership style and motivation contribute to employees. Situational leadership in general has been applied in the environment of EVN, this can be seen from the respondents’ assessment of various indicators of situational leadership, namely the relationship of leaders with subordinates that are well established, the task structure that has been carried out firmly and clearly, the strength of the position of such a good leader. Work motivation for employees in general tends to have increased, especially if it is associated with the support of the work environment for employees to excel, the conditions of mutual respect among employees, as well as the opportunity for employees by the company to develop themselves.